The Benefits of Using the Copilot App in Developing Arabic Vocabulary among Non-Native Learners - ALGAHTANI, ALI SAEED; Al-Yahya, Abdulkarim Saad Saleh (Journal of Cultural Analysis and Social Change, 2025)
This research investigated the impact of the Copilot application on developing vocabulary of learners of Arabic as a second language. To achieve this aim, the research employed both descriptive-analytical and quasi-experimental methodologies. The study involved 25 intermediate-level students at Imam Muhammad ibn Saud Islamic University. The results showed statistically significant differences at the 0.05 level between the mean scores of the experimental group on the two versions of the vocabulary test, favoring the post-test, with a high effect size (0.98). The study recommends encouraging learners to use Copilot for self-learning and research, developing linguistic, research, and analytical skills.